Analisis Proksimat Jagung Pulut (Zea mays L. var Damahu) dari Desa Bontula Kecamatan Asparaga Kabupaten Gorontalo - Mustamin Ibrahim; Devi Bunga Pagalla; Abubakar Sidik Katili; Nurul Fajryani Usman (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
The Damahu waxy corn (Zea mays L. var. Damahu) is a local variety traditionally cultivated by the Gorontalo community and possesses significant potential for the development of functional food products. This study aimed to determine the nutritional composition of the Damahu waxy corn variety originating from Bontula Village, Asparaga District, Gorontalo Regency, through proximate analysis. The corn samples were dried, milled, and analyzed using standard analytical procedures to quantify moisture, ash, fat, protein, and carbohydrate contents. The results indicated that Damahu waxy corn flour contained 83.32% carbohydrates, 5.93% protein, 1.67% fat, 8.84% moisture, and 0.24% ash. This composition characterizes the Damahu variety as a good energy source. However, its protein content does not yet meet the minimum requirement set by the Indonesian National Standard (SNI) for corn-based processed products. The nutritional profile highlights the potential of Damahu waxy corn for the development of nutritious and competitive local food products. This study provides an initial contribution to the documentation of Gorontalo’s indigenous corn varieties and offers a scientific foundation for the utilization of local germplasm to strengthen regional food security.